The Influence of Class Discussion, Communication Skills, Motivation, and Student Satisfaction on Technology Use in Higher Education - Rahman, Zulmi; Habibi, Akhmad; Indryani, Indryani; Nuraini; Anggun, Nurmala (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
The increasing integration of digital technologies in higher education requires a better understanding of the academic and psychological factors that encourage students to adopt technology in learning. This study investigates the influence of class discussion, communication skills, motivation, and student satisfaction on technology use in higher education. A quantitative survey design was employed, involving 317 undergraduate students from two universities in Indonesia selected through purposive sampling. Data were collected using an online questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that communication skills significantly influence motivation, student satisfaction, and technology use, while class discussion significantly enhances motivation and student satisfaction but does not directly affect technology use. Motivation positively influences student satisfaction but shows no significant direct effect on technology use. Student satisfaction emerges as the strongest predictor of technology use, indicating that positive learning experiences encourage students to engage more actively with digital learning technologies. The structural model demonstrates high explanatory and predictive power, supported by substantial R² and Q² values. These findings suggest that higher education institutions should strengthen interactive classroom practices, develop students’ communication competencies, and foster satisfying learning experiences to promote effective technology adoption. This study contributes to the growing body of educational technology literature by highlighting student satisfaction as a central mechanism linking classroom interaction and communication with technology use in higher education.